Parasitic diarrheal disease: drug development and targets - Azam, Amir; Peerzada, Mudasir N.; Ahmad, Kamal (Frontiers in Microbiology, 2015)
Diarrhea is the manifestation of gastrointestinal infection and is one of the major causes of mortality and morbidity specifically among the children of less than 5 years age worldwide. Moreover, in recent years there has been a rise in the number of reports of intestinal infections continuously in the industrialized world. These are largely related to waterborne and food borne outbreaks. These occur by the pathogenesis of both prokaryotic and eukaryotic organisms like bacteria and parasites. The parasitic intestinal infection has remained mostly unexplored and under assessed in terms of therapeutic development. The lack of new drugs and the risk of resistance have led us to carry out this review on drug development for parasitic diarrheal diseases. The major focus has been depicted on commercially available drugs, currently synthesized active heterocyclic compounds and unique drug targets, that are vital for the existence and growth of the parasites and can be further exploited for the search of therapeutically active anti-parasitic agents.